Perioperative course and quality of life in a prospective randomized multicenter phase III trial, comparing standard lobectomy versus anatomical segmentectomy in patients with non-small cell lung cancer up to 2 cm, stage IA (7th edition of TNM staging system) - Stamatis, Georgios; Leschber, Gunda; Schwarz, Birte; Brintrup, Diana Lütke; Ose, Claudia; Weinreich, Gerhard; Passlick, Bernward; Hecker, Erich; Kugler, Christian; Dienemann, Hendrik; Krbek, Thomas; Eggeling, Stephan; et al. (Lung cancer, 2019)
Abstract: Objectives. For early stage non-small cell lung cancer (NSCLC) retrospective data of functionally compromised patients undergoing segmentectomy showed equal outcomes for perioperative complications and quality of life (QoL) compared with lobectomy patients. However no prospectively randomized data comparing patients eligible for both procedures are available.Materials and methods:We conducted a prospective, randomized, multicenter phase III trial and investigated perioperative complications and QoL in patients with NSCLC stage IA (7th edition) undergoing segmentectomy versus lobectomy. The EORTC Questionnaire Core-30 (QLQ C-30) supplemented by thirteen-item lung cancer-specific module (LC13) was assessed before surgery, at discharge, 6 weeks, 3, 6 and 12 months post-surgery.Results: 108 patients with verified or suspected NSCLC up to 2 cm diameter were enrolled, whereby 54 were assigned to lobectomy and 54 to segmentectomy. Due to nodal disease, tumor size and surgical reasons estimated during the operation, eight patients of the segmentectomy group received a lobectomy. In hospital and 90 days mortality was 0% in both groups. Perioperative complications were observed in 6 (11.3%) patients after segmentectomy and in 8 patients (14.8%) after lobectomy (p = 0.563), while the 90-day morbidity were 17% and 25.9% (9 and 14 patients), respectively (p = 0.452). Twelve months after surgery, there was a significant deterioration to the baselines of physical (p < 0.001) and cognitive functioning (p = 0.025), dyspnea (p < 0.001) and fatigue (p = 0.003) in the lobectomy group. Dyspnea showed a faster recovery in the segmentectomy compared to lobectomy group with statistical significance (p = 0.016 after 12 months). Conclusion: In patients with early-stage NSCLC, segmentectomy is associated with a statistically not significant lower perioperative morbidity and appears to provide a superior recovery in QoL compared with lobectomy patients.
Gesehen am 23.04.2020